2020
DOI: 10.1002/cctc.202000608
|View full text |Cite
|
Sign up to set email alerts
|

‘Surface Contrast’ NMR Reveals Non‐innocent Role of Support in Pd/CeO2 Catalyzed Phenol Hydrogenation

Abstract: Ceria (CeO2)‐supported metals are widely used as catalysts because of their exceptional redox properties. Here, we use surface contrast NMR methods to investigate the hydrogenation of phenol by Pd supported on ceria nanoparticles. We show that the rigid and planar binding of phenol to Pd is mediated by a weak and highly mobile association of the small molecule to ceria. Interestingly, while addition of phosphate to the mixture does not perturb the adsorption of phenol on Pd, it destabilizes its interaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
65
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(79 citation statements)
references
References 20 publications
11
65
2
Order By: Relevance
“…The ΔR 2 data measured for PhOH in the presence of the CeO 2 nanorods show the same overall trend observed previously for PhOH adsorption on CeO 2 nanocubes, 7 with the para position displaying larger ΔR 2 than the ortho and meta positions ( Figure 3). This pattern indicates that binding modes (i) and (iii) coexist on the surface of the NP.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…The ΔR 2 data measured for PhOH in the presence of the CeO 2 nanorods show the same overall trend observed previously for PhOH adsorption on CeO 2 nanocubes, 7 with the para position displaying larger ΔR 2 than the ortho and meta positions ( Figure 3). This pattern indicates that binding modes (i) and (iii) coexist on the surface of the NP.…”
Section: Resultssupporting
confidence: 86%
“…In addition, our data revealed that methoxy groups are not capable of effectively hydrogen-bonding to ceria and that PhOH derivatives with an O atom at position 2 form very stable adducts with the Pd sites of Pd/CeO 2 .A comparison of the NMR data with the rate of catalytic hydrogenation measured for the phenolic compounds in the presence of Pd/CeO 2 revealed that % conversion is linearly correlated with the amount of adsorbed small molecule but is inhibited by strong interactions between the substrate and the Pd sites. These data agree with our recent study indicating that the weak interactions between substrate and ceria are competent for catalysis,7 and suggest that stable substrate-Pd adducts may compete with H 2 adsorption and activation and/or reduce catalytic conversion by reducing the rate of product release from the catalyst.Finally, we have shown that13 C ΔR 2 data provide important insight into sorption equilibria. Although they do not return the comprehensive kinetic, thermodynamic, and structural description of NP surface adsorption obtained by a rigorous analysis of a complete set of SC NMR experiments,7 13 C ΔR 2 measurements are less time-consuming and easier to analyze as they do not require extensive modelling and data fitting procedures.…”
supporting
confidence: 92%
See 3 more Smart Citations